First Year's Work Experiences of Foreign Educated Nurses Coming to Norway From Other European Countries - Eva Merethe Solum MA, RPHN, RN; Berit Viken MNSc, RPHN, RN, and; Anne Lyberg MNSc, RPHN RN (SAGE Publishing, 2020)
Introduction Nurses educated in the European Union and European Economic Area are automatically given professional authorization to work in all member states, facilitating workforce mobility between countries. Along with many other European countries, Norway faces nursing shortages in healthcare. European Foreign Educated Nurses are often recruited to work in Norway by agencies or apply for work themselves. Aims To explore the experiences Foreign Educated Nurses from European Union and European Economic Area had with their preparation and orientation programs and their first year of work in Norwegian elderly care institutions Methods The study followed a qualitative explorative design. Nine open, dialogue-based, semi-structured interviews were conducted with Foreign Educated Nurses from Poland, Lithuania, Latvia, Iceland, and Spain. Data were analyzed using qualitative content analysis. Findings One main theme, struggling to adjust to professional competence standards, and four subthemes emerged from our data (1) deficiencies in preparation and orientation by recruitment agencies and institutions, (2) language skills and communication challenges at work, (3) cultural differences in the nursing role in clinical practice, and (4) social interactions at work. Conclusion More comprehensive preparation and orientation programs regarding language skills and local healthcare systems are needed. Foreign Educated Nurses make important contributions to the Norwegian healthcare work force, but the challenges brought to light in this study negatively affected their work conditions and can possibly threaten patient safety. More research is suggested to address the lack of collaboration between agencies, healthcare institutions, and other stakeholders in establishing professional standards and appropriate support for Foreign Educated Nurses from European Union and European Economic Area.